Assessment of Parents’ Knowledge and Confidence in Caring for Children with Asthma: Basis for a Nurse-Led Education Program - Diezma-Bermudez, Katrina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed parents’ knowledge and confidence in caring for children with asthma as basis for developing a nurse-led education program. Anchored on Orem’s Self-Care Deficit Nursing Theory, Bandura’s Social Cognitive Theory, and Leininger’s Culture Care Diversity and Universality Theory, the study employed a quantitative descriptive-correlational design. The respondents were 100 parents or primary caregivers of children diagnosed with asthma who were receiving care in the pediatric ward or outpatient department of a selected Level 3 private hospital in Pasig City, Philippines. Data were gathered using a validated structured questionnaire that measured demographic profile, knowledge, and confidence in asthma care. Frequency, percentage, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient were used to analyze the data. Findings showed that parents had a very high level of knowledge and confidence, with overall means of 3.45 and 3.50, respectively. They were most knowledgeable in recognizing early warning signs and following prescribed asthma management plans, and most confident in asking questions, identifying when emergency care is needed, and actively participating in their child’s care. However, gaps remained in differentiating maintenance and rescue medications, applying environmental control and non-pharmacologic strategies, responding to asthma attacks at home, ensuring follow-through of care instructions, and managing anxiety. Age and gender were significantly related to knowledge and confidence, educational attainment showed a weak negative relationship, and socio-economic status showed no significant relationship. The study recommends strengthening nurse-led asthma education through the proposed BREATHE program, focusing on practical home management, medication use, emergency response, and confidence-building. The study supports SDG 3, SDG 4, SDG 10, and SDG 17 by promoting child health, caregiver education, equitable support, and collaboration in asthma care. Its sustainability impact lies in strengthening public health, family-centered nursing practice, and institutional capacity for chronic disease education.
Keywords: Asthma Care; Confidence; Knowledge; Nurse-Led Education Program; Parents; Pediatric Asthma